Fiscal Responses to Monetary Policy: Insights From a Survey of Government Officials - Andreas Dibiasi; Heiner Mikosch; Samad Sarferaz; Armin Steinbach (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
In a novel survey, we study how German senior government officials systematically adjust fiscal policy in response to economic shocks, focusing on their fiscal responses to a contractionary monetary policy shock. Using randomized vignette treatments, we examine how officials update GDP and inflation expectations under fiscal and monetary policy shock scenarios and assess their preferred fiscal adjustments. Our findings show that officials predominantly respond by increasing debt and reducing spending, with tax increases playing a minor role, often combining multiple fiscal instruments. Counterfactual analysis reveals that officials' reasoning aligns with key insights from the Heterogeneous Agent New Keynesian literature.
Keywords: D83; E62; E63; E52; 330; fiscal policy; monetary policy; fiscal-monetary interaction; expectation formation; survey experiment